The effect of family supportive supervisor behavior on teachers’ innovative behavior and thriving at work: A moderated mediation model - Li, Qiu; Liu, Minghui (Frontiers in Psychology, 2023)
Objective In today’s society, teachers are increasingly focused on the harmonious development of work and family. However, few studies have discussed family supportive supervisor behavior to promote teachers’ innovative behaviors and thriving at work. The study explores the mechanisms of family-supportive supervisor behaviors on teachers’ innovative behaviors and thriving at work. Methods In this study, we adopt a questionnaire-based follow-up study of 409 career married teachers in Northwest China at three time points based on the Work-home Resource Model and Resource Conservation Theory. Results The results indicate that family supportive supervisor behavior has a significant positive predictive effect on teachers’ innovative behavior and thriving at work, and work-family enrichment mediates between this relationship. In addition, proactive personality moderates the relationship between family-supportive supervisor behavior and work-family enrichment and the mediating role of work-family enrichment. Conclusion Prior research has focused more on the impact of job characteristics within the work domain on work innovation behavior and thriving at work, and some studies have explored the impact of family-level factors on teacher behavior, but more often than not, they have been described based on a conflict perspective. This paper explores the positive impact of family-supportive supervisor behavior on teachers’ innovative behaviors and thriving at work from a resource flow perspective and identifies its potential boundary conditions. This study extends theoretical research on family-work relationships while providing new grounding and research perspectives for improving teacher work and family enrichment.